2018
DOI: 10.1007/s40333-018-0013-2
|View full text |Cite
|
Sign up to set email alerts
|

Precipitation amount and frequency affect seedling emergence and growth of Reaumuria soongarica in northwestern China

Abstract: Climate change is shifting the amount and frequency of precipitation in many regions, which is expected to affect seedling recruitment across ecosystems. However, the combined effects of precipitation amount and frequency on seedling recruitment remain largely unknown. An understanding of the effects of precipitation amount and frequency and their interaction on seedling emergence and growth of typical desert plants is vital for managing populations of desert plants. We conducted two experiments to study the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 55 publications
4
12
0
Order By: Relevance
“…This study found that the increase of 30% in precipitation significantly increased the plant height, above-ground biomass, and total biomass of R. soongarica. This result is similar to that of Duan et al and Shan et al [18,20]. However, some studies have suggested that increasing precipitation does not significantly promote the growth of desert plants [10].…”
Section: Impact Of Precipitation On the Growth Of R Soongarica Seedlsupporting
confidence: 91%
See 4 more Smart Citations
“…This study found that the increase of 30% in precipitation significantly increased the plant height, above-ground biomass, and total biomass of R. soongarica. This result is similar to that of Duan et al and Shan et al [18,20]. However, some studies have suggested that increasing precipitation does not significantly promote the growth of desert plants [10].…”
Section: Impact Of Precipitation On the Growth Of R Soongarica Seedlsupporting
confidence: 91%
“…This shows that reducing the frequency of precipitation is better than the frequency-invariant treatment, but the impact is slight. The results are consistent with those of Schneider and Shan [13,20]. Gao et al [11] believed that the values of all nutritional and reproductive traits in plants increase with increasing precipitation frequency.…”
Section: Impact Of Precipitation Frequency On the Growth Of R Soongasupporting
confidence: 88%
See 3 more Smart Citations